An algebra problem by Mark Dave Martin

Algebra Level 2

If f(g(x))=3x+1 and f(x)=3x-2, find g(-2).

-1 -7/3 4 5/2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hansraj Sharma
Aug 10, 2014

let g(x)=ax+b
3(ax+b)-2=3x+1 a=1,b=1 so g(x)=x+1 g(-2)=-1

A much simpler solution which would avoid taking any extra constants would be,

f ( g ( x ) ) = 3 x + 1 f ( x ) = 3 x 2 f(g(x))=3x+1~\land~f(x)=3x-2 3 g ( x ) 2 = 3 x + 1 g ( x ) = x + 1 g ( 2 ) = ( 1 ) \\ \implies 3g(x)-2=3x+1\implies g(x)=x+1 \implies \boxed{g(-2)=(-1)}

Prasun Biswas - 6 years, 4 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...